2014
DOI: 10.1186/1742-2094-11-128
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine pathway disruption in a mouse model of schizophrenia induced by Munc18-1a overexpression in the brain

Abstract: BackgroundAn accumulating body of evidence points to the significance of neuroinflammation and immunogenetics in schizophrenia, and an imbalance of cytokines in the central nervous system (CNS) has been suggested to be associated with the disorder. Munc18-overexpressing mice (Munc18-OE) have provided a model for the study of the alterations that may underlie the symptoms of subjects with schizophrenia. The aim of the present study was to elucidate the involvement of neuroinflammation and cytokine imbalance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Although these studies suggest a correlation between possible astrogliosis and the presence of schizophrenic symptoms, numerous other preclinical studies have reported no changes in GFAP expression associated with schizophrenia. For example, mouse models of schizophrenia with overexpression of Munc-18a or mutant DISC-1 show no changes in cortical or hippocampal GFAP expression, respectively [149, 150].…”
Section: Schizophreniamentioning
confidence: 99%
“…Although these studies suggest a correlation between possible astrogliosis and the presence of schizophrenic symptoms, numerous other preclinical studies have reported no changes in GFAP expression associated with schizophrenia. For example, mouse models of schizophrenia with overexpression of Munc-18a or mutant DISC-1 show no changes in cortical or hippocampal GFAP expression, respectively [149, 150].…”
Section: Schizophreniamentioning
confidence: 99%
“…The same was described for the overexpression of Munc18‐1a , a presynaptic protein that mainly regulates synaptic vesicle fusion by interacting with the SNARE complex (Fig 2 ) and whose mutations or abnormal expression occurs in various neurological diseases, including epileptic encephalopathy, ASD, and schizophrenia. Munc18‐1a overexpression results in immune and inflammatory dysfunctions in distinct brain regions (Gil‐Pisa et al , 2014 ). Interferon‐gamma (IFN‐γ), TNF‐α, IL‐2, and CCL2 chemokine are present at higher levels in the striatum of Munc18‐1a‐overexpressing mice than in WT, while TNF‐α and IL‐2 levels, together with the microglial marker CD11b, are significantly lower in the neocortex.…”
Section: Twist Of the Scene: Do Synaptopathy Genes Activate The Immun...mentioning
confidence: 99%
“…For example, Shen, et al studied whether similar pathways were perturbed in smokers vs. users of e-cigarettes [9]. Gil-Pisa, et al justified the use of their mouse model of schizophrenia based on its similarity in cytokine expression to a previously published model [10]. Martins-de-Souza, et al showed that responders showed the same pathways were affected, but in opposite directions, in poor vs. good responders to anti-psychotics [11].…”
Section: Introductionmentioning
confidence: 99%